A molecular sieve catalyst for methacrylate synthesis and preparation method thereof

By using molecular sieve catalysts in methacrylate catalysts to form a core-shell structure with high specific surface area and structural stability, the problems of easy decomposition and poor reactivity of existing catalysts at high temperatures are solved, and the effect of efficient catalysis and multiple reuses is achieved.

CN119368226BActive Publication Date: 2025-03-04SHANDONG WANDUOFU NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411900187.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-04
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

Existing methacrylate catalysts are easy to decompose at high temperatures, have poor reaction activity, and are difficult to separate effectively, resulting in limited catalytic activity and low yield.

Method used

Using a molecular sieve catalyst, a silica shell is formed by amino-surface A-type microporous molecular sieve surface and combined with ethyl orthosilicate, and rare earth yttrium, zirconium nitrate, cesium nitrate and graphene oxide, forming a core-shell structure with high specific surface area and structural stability.

Benefits of technology

The catalytic performance and reaction conversion rate of the catalyst are significantly improved, the selectivity and yield of methacrylate are enhanced, and the catalyst can be reused many times, maintaining high catalytic activity and selectivity, and extending service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368226B_ABST
    Figure CN119368226B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of methacrylate synthesis, and specifically discloses a molecular sieve catalyst for methacrylate synthesis and a preparation method thereof. The above-mentioned catalyst preparation method includes: adding type A microporous molecular sieve to anhydrous ethanol and ultrasonically treating at room temperature for 1-2h, adding ethylenediamine, stirring at 50-70°C for 1-2h, and removing anhydrous ethanol by rotary evaporation to obtain a pre-treated molecular sieve; adding the pre-treated molecular sieve, yttrium nitrate, and tetraethyl orthosilicate to an ethanol aqueous solution and stirring evenly, adjusting the system pH value to 8-9, 80-90°C insulation for 5-10h, cooling to room temperature, washing, and vacuum drying to obtain a composite molecular sieve; calcining the composite molecular sieve at 300-500°C for 2-4h, cooling to room temperature, adding to water, adding zirconium nitrate, cesium nitrate, and graphene oxide for ultrasonic treatment for 5-10h, standing for 5-10h, 160-190°C hydrothermal reaction for 2-6h, cooling to room temperature, filtering, washing, and vacuum drying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of methacrylate synthesis, and in particular to a molecular sieve catalyst for methacrylate synthesis and a preparation method thereof. Background Art

[0002] At present, methacrylate (MMA) is mainly used in coatings, textiles, adhesives, leather, papermaking, printing and dyeing auxiliaries and other industries. In recent years, the demand for MMA at home and abroad has not only increased, but its application areas have also been continuously expanded, driving the rapid development of the MMA industry.

[0003] The production technology of methyl methacrylate in my country is still in its infancy. Acidic cation exchange resin is commonly used in the industry to produce methyl methacrylate. Although it has good stability, high selectivity and low cost, it has poor heat resistance and is easy to decompose above 250°C. In addition, its specific surface area and pore volume are small, resulting in poor reaction activity and low yield. At present, it is urgent to develop new methacrylate catalysts, improve their catalytic activity, ester selectivity, and enhance their stability.

[0004] CN102850155A discloses a method for preparing methacrylate products, which uses methyl methacrylate and alcohol as raw materials, supplemented with a catalyst and a polymerization inhibitor, and is placed in a reactor for heating and reaction to generate methacrylate products and methanol; then the product is obtained by separation and purification. The catalyst used is a composite of organic tin and titanate, which has limited catalytic activity and is difficult to separate from the reaction system.

[0005] As the demand for methacrylates continues to increase, developing catalysts with excellent performance and improving their catalytic activity and stability are important research directions for researchers in the future. Summary of the invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a molecular sieve catalyst for methacrylate synthesis and a preparation method thereof.

[0007] A method for preparing a molecular sieve catalyst for methacrylate synthesis comprises the following steps:

[0008] S1. Add type A microporous molecular sieve to anhydrous ethanol and perform ultrasonic treatment at room temperature for 1-2 hours, add ethylenediamine, stir at 50-70° C. for 1-2 hours, and remove the anhydrous ethanol by rotary evaporation to obtain a pretreated molecular sieve;

[0009] S2, adding the pretreated molecular sieve, yttrium nitrate and tetraethyl orthosilicate to an ethanol aqueous solution and stirring evenly, adjusting the pH value of the system to 8-9, keeping the temperature at 80-90°C for 5-10h, cooling to room temperature, washing, and vacuum drying to obtain a composite molecular sieve;

[0010] S3. Calcine the composite molecular sieve at 300-500°C for 2-4h, cool to room temperature, add into water, add zirconium nitrate, cesium nitrate and graphene oxide, ultrasonically treat for 5-10h, let stand for 5-10h, hydrothermally react at 160-190°C for 2-6h, cool to room temperature, filter, wash and vacuum dry.

[0011] Preferably, in S1, the mass ratio of type A microporous molecular sieve to ethylenediamine is 5-10:0.1-1.

[0012] Preferably, in S1, the ultrasonic frequency is 5-10 kHz.

[0013] Preferably, in S2, the mass ratio of the pretreated molecular sieve, yttrium nitrate and tetraethyl orthosilicate is 6-12:0.01-0.1:3-8.

[0014] Preferably, in S2, the mass fraction of the ethanol aqueous solution is 40-60%.

[0015] Preferably, in S2, after adjusting the pH value of the system to 8-9, the insulation process is carried out at a insulation pressure of 1-2.5 MPa.

[0016] Preferably, the specific surface area of ​​the composite molecular sieve obtained by S2 is 605-712m 2 / g, the pore volume is 1.7-1.95mL / g, and the average pore diameter is 5-15nm.

[0017] Preferably, in S3, the mass ratio of the composite molecular sieve, zirconium nitrate, cesium nitrate and graphene oxide is 8-16:1-2:1-2:1-3.

[0018] Preferably, in S3, the ultrasonic frequency is 5-10 kHz.

[0019] A molecular sieve catalyst for methacrylate synthesis is prepared by the above-mentioned molecular sieve catalyst preparation method for methacrylate synthesis. Beneficial effect: After the surface of the A-type microporous molecular sieve is aminated, it is combined with ethyl orthosilicate to form a layer of silicon dioxide shell on the surface of the A-type microporous molecular sieve. The core-shell structure formed after calcination not only has a large specific surface area, but also has extremely high bonding strength of rare earth yttrium on the composite molecular sieve, and is further combined with zirconium nitrate, cesium nitrate, and graphene oxide, and has high structural stability.

[0020] The present invention loads yttrium nitrate, zirconium nitrate and cesium nitrate in steps, which can not only effectively avoid aggregation and ensure their respective high dispersibility, but also expose more active centers in cooperation with lamellar graphene oxide, have high catalytic activity, effectively slow down the deactivation of the catalytic process, and achieve good catalyst reuse effect.

[0021] The applicant has found that the present invention can greatly improve the catalytic performance of the catalyst, improve the reaction conversion rate, and improve the selectivity and yield of the target product MMA; and can be reused multiple times while maintaining high catalytic activity and selectivity, thereby extending the service life of the catalyst.

[0022] The invention helps the effective diffusion of raw materials and product molecules during the esterification reaction, has strong catalytic ability, is not easy to swell and deform during catalytic synthesis, has good heat resistance and repeatability, and has a simple preparation method, which is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a comparison chart of the specific surface area and pore volume of the composite molecular sieves obtained in Example 5 and Comparative Examples 1-2.

[0024] Figure 2 It is a comparison chart of formaldehyde conversion rate and methyl propionate conversion rate after the molecular sieve catalysts obtained in Example 5 and Comparative Examples 1-2 participate in the catalytic reaction.

[0025] Figure 3 This is a comparison chart of methacrylate selectivity and methacrylate yield after the molecular sieve catalysts obtained in Example 5 and Comparative Examples 1-2 participated in the catalytic reaction.

[0026] Figure 4 It is a comparison chart of the cyclic catalytic performance of the molecular sieve catalysts obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0027] The present invention will be further explained below in conjunction with specific embodiments.

[0028] The 5A molecular sieve used in the following was purchased from Ningbo Mouci Environmental Protection Technology Co., Ltd.

[0029] Example 1: A method for preparing a molecular sieve catalyst for methacrylate synthesis, comprising the following steps:

[0030] S1. Add 5 g of 5A molecular sieve to 20 g of anhydrous ethanol, ultrasonically treat at room temperature for 1 h at an ultrasonic frequency of 5 kHz, add 0.1 g of ethylenediamine, stir at 50 °C for 1 h, and remove the anhydrous ethanol by rotary evaporation to obtain a pretreated molecular sieve;

[0031] S2, add 6g of pretreated molecular sieve, 0.01g of yttrium nitrate, and 3g of tetraethyl orthosilicate to 40g of 40% ethanol aqueous solution and stir evenly, adjust the pH value of the system to 8-9 with ammonia water, send it into a high-pressure reactor, keep it at 80°C for 5h, and keep it at a pressure of 1MPa, cool it to room temperature, wash it with deionized water, and vacuum dry it to obtain a composite molecular sieve;

[0032] S3. Calcine 8 g of the composite molecular sieve at 300 °C for 2 h, cool to room temperature, add 50 g of deionized water, add 1 g of zirconium nitrate, 1 g of cesium nitrate, and 1 g of graphene oxide, and ultrasonically treat for 5 h at an ultrasonic frequency of 5 kHz. Let stand for 5 h, hydrothermally react at 160 °C for 2 h, cool to room temperature, filter, wash, and vacuum dry.

[0033] Example 2: A method for preparing a molecular sieve catalyst for methacrylate synthesis, comprising the following steps:

[0034] S1. Add 10 g of 5A molecular sieve to 40 g of anhydrous ethanol, ultrasonically treat at room temperature for 2 h at an ultrasonic frequency of 10 kHz, add 1 g of ethylenediamine, stir at 70 ° C for 2 h, and remove the anhydrous ethanol by rotary evaporation to obtain a pretreated molecular sieve;

[0035] S2, 12g of pretreated molecular sieve, 0.1g of yttrium nitrate, and 8g of tetraethyl orthosilicate were added to 70g of 60% ethanol aqueous solution and stirred evenly, and the pH value of the system was adjusted to 8-9 with ammonia water, and the mixture was sent to a high-pressure reactor, and kept at 90°C for 10h, and the insulation pressure was 2.5MPa, and then cooled to room temperature, washed with deionized water, and vacuum dried to obtain a composite molecular sieve;

[0036] S3. Calcine 16 g of the composite molecular sieve at 500°C for 4 h, cool to room temperature, add 100 g of deionized water, add 2 g of zirconium nitrate, 2 g of cesium nitrate, and 3 g of graphene oxide, and ultrasonically treat for 10 h at an ultrasonic frequency of 10 kHz. Let stand for 10 h, hydrothermally react at 190°C for 6 h, cool to room temperature, filter, wash, and vacuum dry.

[0037] Example 3: A method for preparing a molecular sieve catalyst for methacrylate synthesis, comprising the following steps:

[0038] S1. Add 7 g of 5A molecular sieve to 35 g of anhydrous ethanol, ultrasonically treat at room temperature for 80 min at an ultrasonic frequency of 8 kHz, add 0.3 g of ethylenediamine, stir at 65 °C for 80 min, and remove the anhydrous ethanol by rotary evaporation to obtain a pretreated molecular sieve;

[0039] S2, 10g of pretreated molecular sieve, 0.03g of yttrium nitrate, and 6g of tetraethyl orthosilicate were added to 50g of 55% ethanol aqueous solution and stirred evenly, and the pH value of the system was adjusted to 8-9 with ammonia water, and the mixture was sent to a high-pressure reactor, and kept at 82°C for 9h, and the insulation pressure was 1.5MPa, and then cooled to room temperature, washed with deionized water, and vacuum dried to obtain a composite molecular sieve;

[0040] S3. Calcine 14 g of the composite molecular sieve at 350°C for 3.5 h, cool to room temperature, add 70 g of deionized water, add 1.8 g of zirconium nitrate, 1.3 g of cesium nitrate, and 2.5 g of graphene oxide, and ultrasonically treat for 7 h at an ultrasonic frequency of 8 kHz. Let stand for 7 h, hydrothermally react at 180°C for 3 h, cool to room temperature, filter, wash, and vacuum dry.

[0041] Example 4: A method for preparing a molecular sieve catalyst for methacrylate synthesis, comprising the following steps:

[0042] S1, add 9g 5A molecular sieve to 25g anhydrous ethanol, ultrasonically treat at room temperature for 100min, the ultrasonic frequency is 6kHz, add 0.7g ethylenediamine, stir at 55°C for 100min, and remove anhydrous ethanol by rotary evaporation to obtain a pretreated molecular sieve;

[0043] S2, 8g of pretreated molecular sieve, 0.07g of yttrium nitrate, and 4g of tetraethyl orthosilicate were added to 60g of 45% ethanol aqueous solution and stirred evenly, and the pH value of the system was adjusted to 8-9 with ammonia water, and the mixture was sent to a high-pressure reactor, and kept at 88°C for 7h, and the insulation pressure was 2MPa, and then cooled to room temperature, washed with deionized water, and vacuum dried to obtain a composite molecular sieve;

[0044] S3. Calcine 10 g of the composite molecular sieve at 450°C for 2.5 h, cool to room temperature, add 90 g of deionized water, add 1.2 g of zirconium nitrate, 1.7 g of cesium nitrate, and 1.5 g of graphene oxide, and ultrasonically treat for 9 h at an ultrasonic frequency of 6 kHz. Let stand for 9 h, hydrothermally react at 170°C for 5 h, cool to room temperature, filter, wash, and vacuum dry.

[0045] Example 5: A method for preparing a molecular sieve catalyst for methacrylate synthesis, comprising the following steps:

[0046] S1, add 8g 5A molecular sieve to 30g anhydrous ethanol, ultrasonically treat at room temperature for 90min, the ultrasonic frequency is 7.5kHz, add 0.5g ethylenediamine, stir at 60°C for 90min, and remove anhydrous ethanol by rotary evaporation to obtain a pretreated molecular sieve;

[0047] S2, 9g of pretreated molecular sieve, 0.05g of yttrium nitrate, and 5g of tetraethyl orthosilicate were added to 55g of 50% ethanol aqueous solution and stirred evenly, and the pH value of the system was adjusted to 8-9 with ammonia water, and the mixture was sent to a high-pressure reactor, and kept at 85°C for 8h, and the insulation pressure was 1.8MPa, and then cooled to room temperature, washed with deionized water, and vacuum dried to obtain a composite molecular sieve;

[0048] S3. Calcine 12 g of the composite molecular sieve at 400 °C for 3 h, cool to room temperature, add 80 g of deionized water, add 1.5 g of zirconium nitrate, 1.5 g of cesium nitrate, and 2 g of graphene oxide, and ultrasonically treat for 8 h at an ultrasonic frequency of 7.5 kHz. Let stand for 8 h, hydrothermally react at 175 °C for 4 h, cool to room temperature, filter, wash, and vacuum dry.

[0049] Comparative Example 1: A method for preparing a molecular sieve catalyst for methacrylate synthesis, comprising the following steps:

[0050] S1, add 8g 5A molecular sieve to 30g anhydrous ethanol, ultrasonically treat at room temperature for 90min, the ultrasonic frequency is 7.5kHz, add 0.5g ethylenediamine, stir at 60°C for 90min, and remove anhydrous ethanol by rotary evaporation to obtain a pretreated molecular sieve;

[0051] S2, 9g of pretreated molecular sieve and 5g of ethyl orthosilicate were added to 55g of 50% ethanol aqueous solution and stirred evenly, and the pH value of the system was adjusted to 8-9 with ammonia water, and the mixture was sent to a high-pressure reactor, and the temperature was kept at 85°C for 8h, and the insulation pressure was 1.8MPa, and then the mixture was cooled to room temperature, washed with deionized water, and vacuum dried to obtain a composite molecular sieve;

[0052] S3. Calcine 12 g of the composite molecular sieve at 400 °C for 3 h, cool to room temperature, add 80 g of deionized water, add 0.05 g of yttrium nitrate, 1.5 g of zirconium nitrate, 1.5 g of cesium nitrate, and 2 g of graphene oxide, and ultrasonically treat for 8 h at an ultrasonic frequency of 7.5 kHz. Let stand for 8 h, hydrothermally react at 175 °C for 4 h, cool to room temperature, filter, wash, and vacuum dry.

[0053] Comparative Example 2: A method for preparing a molecular sieve catalyst for methacrylate synthesis, comprising the following steps:

[0054] S1, add 8g 5A molecular sieve to 30g anhydrous ethanol, ultrasonically treat at room temperature for 90min, the ultrasonic frequency is 7.5kHz, add 0.5g ethylenediamine, stir at 60°C for 90min, and remove anhydrous ethanol by rotary evaporation to obtain a pretreated molecular sieve;

[0055] S2, adding 0.05g of yttrium nitrate and 5g of tetraethyl orthosilicate to 55g of 50% by mass ethanol aqueous solution and stirring evenly, adjusting the pH value of the system to 8-9 with ammonia water, sending it into a high-pressure reactor, keeping it at 85°C for 8h, the insulation pressure is 1.8MPa, cooling it to room temperature, washing it with deionized water, vacuum drying, and then adding 9g of pretreated molecular sieve to mix to obtain a composite molecular sieve;

[0056] S3. Calcine 12 g of the composite molecular sieve at 400 °C for 3 h, cool to room temperature, add 80 g of deionized water, add 1.5 g of zirconium nitrate, 1.5 g of cesium nitrate, and 2 g of graphene oxide, and ultrasonically treat for 8 h at an ultrasonic frequency of 7.5 kHz. Let stand for 8 h, hydrothermally react at 175 °C for 4 h, cool to room temperature, filter, wash, and vacuum dry.

[0057] The specific surface area and pore volume of the composite molecular sieve S2 obtained in Example 5 and Comparative Example 1-2 were measured using the BET method. Figure 1 As shown, the specific surface area of ​​the composite molecular sieve obtained in Example 5 is the largest, which is better than that of Comparative Examples 1-2 (P < 0.05); at the same time, the pore volume of the composite molecular sieve obtained in Example 5 is slightly inferior to that of Comparative Example 1, but there is no significant difference (P > 0.05), and it is better than Comparative Example 2 (P < 0.05).

[0058] The applicant believes that this is probably because yttrium nitrate was not deposited on the surface of the molecular sieve, resulting in differences in specific surface area and pore volume of the composite molecular sieve obtained in Example 5 and Comparative Example 1.

[0059] The molecular sieve catalysts obtained in Example 5 and Comparative Example 2 were used for the synthesis of methacrylate, specifically as follows: each group of samples was filled in a fixed bed reactor, the molar ratio of formaldehyde to methyl propionate was 1:5, and the feed space velocity was 3.5 h -1 , the reaction temperature is 350°C and the reaction pressure is 0.15MPa.

[0060] The liquid products obtained after the reaction were quantitatively analyzed by gas chromatography, and the chromatographic conditions were as follows: injection port temperature 150°C, detector temperature 250°C, column box temperature was programmed to rise from 80°C for 5 min, 15°C / min to 190°C for 5 min, and then to 220°C for 1 min. The split ratio was 20:1, and the carrier gas was high-purity nitrogen at a pressure of 0.4 MPa.

[0061] Calculate each indicator according to the following formula:

[0062] Formaldehyde conversion rate (mo1%) = the amount of reacted formaldehyde / the amount of supplied formaldehyde × 100%

[0063] Methyl propionate conversion rate (mol%) = amount of methyl propionate reacted ÷ amount of methyl propionate supplied × 100%

[0064] Methacrylate selectivity (mo1%) = the amount of methacrylate produced ÷ the amount of methyl propionate supplied × 100%

[0065] Methacrylate yield (%) = methyl propionate conversion × methacrylate selectivity × 100

[0066] like Figure 2 and Figure 3 As shown, when the molecular sieve catalyst obtained in Example 5 was used for catalytic reaction, the formaldehyde conversion rate, methyl propionate conversion rate, methacrylate selectivity and methacrylate yield were all the highest, which were better than those of Comparative Examples 1-2 (P < 0.05).

[0067] Each group of molecular sieve catalysts after the above catalytic reaction was taken out, calcined at 450°C for regeneration, and then the catalytic reaction was continued. This process was repeated 5 times, and the methacrylate selectivity was used to characterize the cyclic performance of each group of catalysts.

[0068] like Figure 4 As shown, after 5 cycles, the catalytic performance of each group of molecular sieve catalysts decreased. This is because during the cyclic catalytic process, products are continuously deposited on the catalyst surface, which reduces the specific surface area and covers the active centers, resulting in partial deactivation of the catalyst. The catalytic performance of the molecular sieve catalyst obtained in Example 5 is always better than that of Comparative Examples 1-2 (P < 0.05).

[0069] The applicant believes that the reason for the above results is that the present invention is combined with tetraethyl orthosilicate after the surface of the A-type microporous molecular sieve is aminated, thereby forming a layer of silicon dioxide shell on the surface of the A-type microporous molecular sieve, and the core-shell structure formed after calcination is not only large in specific surface area, but also extremely high in binding strength of rare earth yttrium on the composite molecular sieve, and further combined with zirconium nitrate, cesium nitrate, and graphene oxide, and the structural stability is high. At the same time, the present invention loads yttrium nitrate with zirconium nitrate and cesium nitrate step by step, which can not only effectively avoid aggregation, but also ensure high dispersibility of each, and expose more active centers under the cooperation of lamellar graphene oxide, and the catalytic activity is high, and the deactivation of the catalytic process is effectively slowed down, and the catalyst is reused with good effect. The present invention contributes to the effective diffusion of raw materials and product molecules in the esterification reaction process, has strong catalytic ability, is not easy to swell and deform in catalytic synthesis, and has good heat resistance and repeatability.

[0070] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a molecular sieve catalyst for methacrylate synthesis, characterized in that: The steps include: S1. Add type A microporous molecular sieve to anhydrous ethanol and perform ultrasonic treatment at room temperature for 1-2 hours, add ethylenediamine, stir at 50-70° C. for 1-2 hours, and remove the anhydrous ethanol by rotary evaporation to obtain a pretreated molecular sieve; S2, adding the pretreated molecular sieve, yttrium nitrate and tetraethyl orthosilicate to an ethanol aqueous solution and stirring evenly, adjusting the pH value of the system to 8-9, keeping the temperature at 80-90°C for 5-10h, cooling to room temperature, washing, and vacuum drying to obtain a composite molecular sieve; In S2, the mass ratio of pretreated molecular sieve, yttrium nitrate, and tetraethyl orthosilicate is 6-12: 0.01-0.1: 3-8; S3, calcining the composite molecular sieve at 300-500°C for 2-4h, cooling to room temperature, adding water, adding zirconium nitrate, cesium nitrate, and graphene oxide, ultrasonically treating for 5-10h, standing for 5-10h, hydrothermally reacting at 160-190°C for 2-6h, cooling to room temperature, filtering, washing, and vacuum drying; In S3, the mass ratio of the composite molecular sieve, zirconium nitrate, cesium nitrate and graphene oxide is 8-16:1-2:1-2:1-3.

2. The method for preparing a molecular sieve catalyst for methacrylate synthesis according to claim 1, characterized in that: In S1, the mass ratio of type A microporous molecular sieve to ethylenediamine is 5-10:0.1-1.

3. The method for preparing a molecular sieve catalyst for methacrylate synthesis according to claim 1, characterized in that: In S1, the ultrasound frequency is 5-10kHz.

4. The method for preparing a molecular sieve catalyst for methacrylate synthesis according to claim 1, characterized in that: In S2, the mass fraction of the ethanol aqueous solution is 40-60%.

5. The method for preparing a molecular sieve catalyst for methacrylate synthesis according to claim 1, characterized in that: In S2, the pH value of the system is adjusted to 8-9 and then the insulation process is carried out, and the insulation pressure is 1-2.5MPa.

6. The method for preparing a molecular sieve catalyst for methacrylate synthesis according to claim 1, characterized in that: The specific surface area of ​​the composite molecular sieve obtained by S2 is 605-712m 2 / g, the pore volume is 1.7-1.95mL / g, and the average pore diameter is 5-15nm.

7. The method for preparing a molecular sieve catalyst for methacrylate synthesis according to claim 1, characterized in that: In S3, the ultrasound frequency is 5-10kHz.

8. A molecular sieve catalyst for methacrylate synthesis, characterized in that: The catalyst is prepared by the method for preparing a molecular sieve catalyst for methacrylate synthesis according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of methacrylate products

    CN102850155A

  • Preparation method and application of Pt-K bimetallic molecular sieve catalyst

    CN117443442A

  • Process for preparing methacrylic or acrylic esters

    CN1230169A